A Pragmatic Study of Dysphemism in Steven Berkoff’s Play East (Journal of Namibian Studies : History Politics Culture, 2023)
The present study pragmatically explores categories and functions of dysphemisms in Steven Berkoff’s play East. The objective of the paper is to explore the characters’ use of dysphemism; its categories and functions and apply Allan and Burridge’s (2006) classification of dysphemism, Goffman’s (1962) notion of face, and Brown and Levinson’s (1987) theory of politeness to the play. To gather and examine the text, the researcher adopts a qualitative descriptive approach which involves the researcher himself being the instrument who does everything. The data are taken from the script that is read and re-read to identify the dysphemistic expressions and then coded to be analyzed by using a qualitative discourse analysis method. The results of the paper reveal that all characters use all the categories of dysphemism; insult is the most used followed by profanity and obscenity. In addition, they utilize dysphemism to express hatred, anger, and disrespect, ridicule, and insult each other. Besides, they do not mitigate their expressions and attack each other positive face and the audience’s positive face too. The findings of the study are beneficial to pupils, teachers, writers, journalists, TV producers, footballers, orators, filmmakers, and politicians who are anticipated to be familiar with the dysphemistic terms in order to avoid them and use neutral ones as alternatives.